SOLIDARITAS SOSIAL MAHASISWA PERANTAUAN SUKU BATAK KARO DI UNIVERSITAS SAM RATULANGI - Sabarita Br Sembiring (HOLISTIK, Journal of Social and Culture, 2023)
Man is said to be a social creature can be interpreted to mean that he is born to relate and get along with his fellow man, therefore he cannot live alone. In human nature it is part of a social organization because almost all human activities are carried out in relation to others and in common life with other human beings. Consciousness in human beings is also one of the most important factors for creating solidarity. Solidarity may be a very easy thing for many people to do, but once we understand how important it is in our lives, it is only right that we instill that solidarity is there and not lost. In the campus life environment of Batak Karo students such as in faculties, cafes, and places of worship. With this environment, Batak Karo students interact with each other, even interacting with other tribes in Manado. Likewise, for students at Sam Ratulangi University, there is a special Batak Karo student association organization called PERMAKAN which means the unity of Karo youth in Manado For Batak Karo students, building communication between ethnicities is an obligation. Forming groups in Manado City is one way they can maintain relations between ethnicities, then they carry out and preserve the values, norms, customs, and customs of the Batak Karo Tribe in Manado City. So that it can foster a high sense of solidarity, and can maintain and preserve values, norms and customs in Manado City. Keywords: social solidarity, overseas students, Batak Karo